2017
DOI: 10.1371/journal.pone.0188652
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimental nitrogen fertilization on planktonic metabolism and CO2 flux in a hypereutrophic hardwater lake

Abstract: Hardwater lakes are common in human-dominated regions of the world and often experience pollution due to agricultural and urban effluent inputs of inorganic and organic nitrogen (N). Although these lakes are landscape hotspots for CO2 exchange and food web carbon (C) cycling, the effect of N enrichment on hardwater lake food web functioning and C cycling patterns remains unclear. Specifically, it is unknown if different eutrophication scenarios (e.g., modest non point vs. extreme point sources) yield consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 85 publications
7
48
0
Order By: Relevance
“…It is interesting that TN, and not TP, emerged as the strongest proxy of trophic status when considering the entire methanotrophic community. This result in no way diminishes the role of P in determining aquatic productivity, but underlines the importance of N in these boreal inland waters, as has been highlighted in a recent study (Bogard et al, ). Despite the fact that those environmental factors were selected statistically, their explanatory power remained generally low in both the partial Mantel and MRT analyses.…”
Section: Discussionsupporting
confidence: 66%
“…It is interesting that TN, and not TP, emerged as the strongest proxy of trophic status when considering the entire methanotrophic community. This result in no way diminishes the role of P in determining aquatic productivity, but underlines the importance of N in these boreal inland waters, as has been highlighted in a recent study (Bogard et al, ). Despite the fact that those environmental factors were selected statistically, their explanatory power remained generally low in both the partial Mantel and MRT analyses.…”
Section: Discussionsupporting
confidence: 66%
“…Light availability directly regulates phytoplankton photosynthesis and subsequent growth and is determined by incident solar irradiance, vertical light attenuation and mixing depth of the water column (Krause‐Jensen & Sand‐Jensen, ; Wofsy, ). Availability of nitrogen and phosphorus frequently limits formation of essential structural and catalytic cell pools and, thereby, influences rates of photosynthesis and growth as well as the maximum attainable biomass (Bogard et al., ; Phillips et al., ; Spijkerman, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it was never tested whether supplementary addition of DIC could have increased the biomass even further. Recent laboratory and modelling work (Verspagen, van de Waal, Finke, Visser, & Huisman, ; Verspagen, van de Waal, Finke, Visser, Van Donk et al., ) as well as mesocosm studies (Bogard et al., ; Low‐DĂ©carie, Bell, & Fussmann, ) have shown that greater DIC supply stimulates short‐term phytoplankton biomass development and productivity in eutrophic or eutrophied lakes of low‐medium DIC content. Moreover, cyanobacterial surface blooms are stimulated by higher atmospheric CO 2 and water DIC concentrations (Ibelings & Maberly, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations